2000
DOI: 10.1152/jappl.2000.89.5.1956
|View full text |Cite
|
Sign up to set email alerts
|

Arterial properties of the carotid and femoral artery in endurance-trained and paraplegic subjects

Abstract: In humans, the relationships of blood flow changes to structure, function, and shear rate of conducting arteries have not been thoroughly examined. Therefore, the purpose of this study was to investigate these parameters of the elastic-type, common carotid artery (CCA) and the muscular-type, common femoral artery (CFA) in long-term highly active and extremely inactive individuals, assuming that the impact of activity-induced blood flow changes on conduit arteries, if any, should be seen in these subjects. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
112
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 34 publications
(35 reference statements)
13
112
1
4
Order By: Relevance
“…54,55 Compared with the inactive lower limbs, the active upper limb vasculature is relatively well preserved. For example, the diameters of the common carotid artery 51,53 and brachial artery 50 are similar between SCI and AB. Thus, it appears the structural adaptations below the injury are primarily an adaptation to the reduced metabolic demands of the lower limb vasculature.…”
Section: Conduit Arterial Function After Sci Structural Adaptationsmentioning
confidence: 98%
See 2 more Smart Citations
“…54,55 Compared with the inactive lower limbs, the active upper limb vasculature is relatively well preserved. For example, the diameters of the common carotid artery 51,53 and brachial artery 50 are similar between SCI and AB. Thus, it appears the structural adaptations below the injury are primarily an adaptation to the reduced metabolic demands of the lower limb vasculature.…”
Section: Conduit Arterial Function After Sci Structural Adaptationsmentioning
confidence: 98%
“…However, shear stress and shear rate in the common femoral artery in individuals with SCI are Peripheral vascular function in spinal cord injury CR West et al 50-100% greater than in AB individuals. 51,53,54 The almost doubled shear rate appears to be a consequence of the inactivity rather than loss of supraspinal sympathetic control, as both tetraplegics (decreased sympathetic tone to a nearly all of the vasculature) and low paraplegics (decreased sympathetic tone to approximately half of the vasculature) demonstrate similar increases in shear stress compared with AB controls. 51 It should be noted that shear stress is inversely proportional to arterial diameter cubed at constant flow and viscosity.…”
Section: Conduit Arterial Function After Sci Structural Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the former, recent research has shown that individuals with complete SCI exhibit peripheral vascular changes that likely contribute to their increased cardiovascular risk. Specifically, studies have found the luminal diameter to be significantly reduced 20 and the vascular resistance to be significantly increased 6,21 in the femoral artery of individuals with complete SCI, and accordingly, resting femoral artery blood flow may be reduced by approximately 50% compared to that of able-bodied individuals. 4 Clinically, this reduction in blood flow has been hypothesized to contribute to thrombus formation, 3,4 delayed wound healing 21 and an increased risk of pressure sore formation.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study suggest that decreased compliance of peripheral small arteries may partly reduce peripheral blood flow, resulting in reduction in muscle volume in middle-aged and elderly individuals. On the other hand, recent studies have shown that moderate or high-intensity physical training induced an increase in the diameter of the femoral artery [29][30][31] , whereas femoral arterial compliance did not change in contrast with carotid arterial compliance 32) . Also, a previous study indicated that resistance training increased blood flow and vascular conductance of the femoral artery in middle-aged and elderly adults 33) .…”
Section: Discussionmentioning
confidence: 78%